LEARNING STYLES AND LEXICAL PRESENTATION MODES - Kassaian, Zohreh (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The present study investigated the effect of two types of teaching methods on the retention of unfamiliar words. Sixty-six university students having either auditory or visual learning styles participated in teaching method environments which were either visual or aural. The retention of the vocabulary items was measured by tests of recall and recognition immediately after each training session, and after one week. Data analyses indicated that: 1) the subjects with visual style of learning retained vocabulary items they had learned visually better than the items they had learned aurally, but the subjects with aural style of learning did not show better retention for items they had learned aurally, 2) all the subjects retained visually presented items better than aurally presented items in the immediate and delayed tests, 3) the type of test, that is, recognition or recall, did not have any significant effect on the retention of visually/aurallypresented items , 4) the participants performed better in recognition test than in recall test for both aurally- and visually-presented items, 5) memory loss was greater for visually learned items compared to aurally learned items after one week. Resumen En esta investigación se ha estudiado el efecto de dos estilos de enseñanza relacionados con la presentación de vocabulario. Sesenta y seis estudiantes universitarios con estilos de aprendizaje oral y visual participaron en un estudio en dos contextos de aprendizaje en los que se favorecía el aprendizaje oral o visual. La retención de vocabulario se midió con pruebas de memoria y reconocimiento inmediatamente después de cada sesión de aprendizaje y después de una semana. El análisis de la información recabada indicó que: 1) Los sujetos con un estilo visual de aprendizaje retenían mejor el vocabulario aprendido de forma visual, pero lo sujetos con un estilo de aprendizaje oral no mostraban mejor retención de los vocablos que habían aprendido de forma oral, 2) todos los sujetos retuvieron el vocabulario presentado de forma visual mejor que el presentado de forma oral, tanto en las pruebas inmediatas como en las retrasadas, 3) el tipo de prueba, reconocimiento o recuerdo, no tenía una correlación significativa en la retención del vocabulario presentado de forma visual u oral, 4) los participantes obtuvieron mejores resultados en el test de reconocimiento que en el test de recuerdo tanto para el vocabulario presentado de forma oral como el presentado de forma visual, 5) el olvido fue mayor para el vocabulario aprendido de forma visual comparado con el aprendido de forma oral, una semana más tarde.